1978
DOI: 10.1002/pol.1978.180160313
|View full text |Cite
|
Sign up to set email alerts
|

Conformational transition of copolymer of maleic acid and styrene in aqueous solution. III

Abstract: Kinetic studies of the pH‐induced conformational transition of the hydrophobic copolyelectrolyte of maleic acid and styrene in aqueous NaCl at ionic strength 0.09 were performed by an optical method at 25.0°C with a rapid reaction analyzer of high resolving power. A pH jump applied to a solution, in which the molecule is in the compact form, gives a kinetic trace from which, by appling the general kinetic theory of cooperative transitions, two mean relaxation times are determined. Plots of these relaxation tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

1982
1982
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…It has been shown that in the presence of organic molecules the chains of PMA aggregate around the fluorescent probe forming a cluster. These (15) clusters are formed at low pH, 13 and they are stable up to pH 6. 31 Therefore, we can conclude that the conformational transition that takes PMA from an extended to the contracted state occurs in at least three different steps involving different structures: The first is very fast and cannot be observed by the stopped-flow technique.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been shown that in the presence of organic molecules the chains of PMA aggregate around the fluorescent probe forming a cluster. These (15) clusters are formed at low pH, 13 and they are stable up to pH 6. 31 Therefore, we can conclude that the conformational transition that takes PMA from an extended to the contracted state occurs in at least three different steps involving different structures: The first is very fast and cannot be observed by the stopped-flow technique.…”
Section: Resultsmentioning
confidence: 96%
“…1,14,15 In this model, the transition is described as occurring between two forms, A and B, in which the polymer subunits may exist. At low values of R the form A dominates, and after passing the transition region the B form will occur predominantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyelectrolytes with hydrophobic groups attached to the side chain may give rise to intramolecular micelles under appropriate conditions. Such polymers have been called "polysoaps", and typical examples are the n-dodecyl derivatives of poly(4-vinylpyridine); 1 copolymers of maleic acid with alkyl vinyl ethers, [2][3][4][5][6][7] styrene, [8][9][10][11] or R-methylstyrene. 12 These polymers are known to form hydrophobic microdomains as a consequence of a pH-induced conformational transition, and this process has been studied by different measuring techniques.…”
Section: Introductionmentioning
confidence: 99%
“…6,12,13 A similar pH-induced conformational transition has been observed in an alternating copolymer of maleic acid and styrene. [8][9][10][11] In this polymer, the compact form is stabilized by hydrophobic interaction between phenyl groups, and the transition occurs near R 1 ) 0.3.…”
Section: Introductionmentioning
confidence: 99%